Interannual variation of chlorophyll-a concentration in the exclusive economic zone waters of Peninsular Malaysia - Mustapha M.A.,; Lihan T.,; Zambari I.F., (Penerbit Universiti Kebangsaan Malaysia, 2017)
Chlorophyll-a concentration is one of the major indicators of phytoplankton production in the ocean. Identification of chlorophyll-a distribution and productivity is important to understand physical and biological processes in the ocean. The objectives of this study are to determine the spatial and temporal distribution of chlorophyll-a and to identify influence of sea surface temperature (SST) and current on chlorophyll-a concentration variation in the Exclusive Economic Zone (EEZ) waters of Peninsular Malaysia. Satellite data of chlorophyll-a concentration and SST (2007 to 2014) were derived from MODISAqua and geostrophic current was obtained from NOAA Ocean Watch. Empirical Orthogonal Function (EOF) analysis was used to determine the spatial and temporal variation of chlorophyll-a. Five modes represented the variation of chlorophyll-a. Mode 1 (60.62%) explained seasonal pattern, Mode 2 (27.83%) indicated patterns during the southwest monsoon, Mode 3 (19.96%) highlighted the inter monsoon of northeast to southwest. Mode 4 (19.57%) represented the northeast monsoon and Mode 5 (18.98%) explained inter monsoon of southwest to northeast. Variation of chlorophyll-a concentration was influenced by variability in SST and current during the monsoons. Variability in magnitude and direction of current circulation was observed to affect SST distribution thus influences concentration and distribution of chlorophyll-a.